A SYNTACTICAL ANALYSIS ON SENTENCE PATTERNS USED IN BARACK OBAMA SPEECH - Manossoh, Jeniver R.; Samola, Nurmin; Olii, Sanerita T. (Journal of English Culture, Language, Literature and Education, 2022)
This study focuses on 9 basic sentence patterns that used in Barack Obama speech which he delivered when visited Universitas Indonesia Jakarta. The aim of the study is to find out how many sentence patterns that used in Barack Obama Speech. This study used qualitative research which the researcher analyzed through the script. The results of the study showed that there were 8 sentence patterns in the speech as follows, they were pattern 1 (9 sentences), pattern 2 (2 sentences), pattern 3 (26 sentences), pattern 4 (1 sentence), pattern 6 (20 sentences), pattern 7 (103 sentences), pattern 8 (1 sentence), pattern 9 (2 sentences). Based on the result, it can be concluded that the pattern 7 were most dominant of the other pattern, then there was 1 pattern was not found, pattern 5. In this research there were various kinds of sentences pattern in 1 speech that can be used to help you improve writing skill, for English learners especially for the future researchers